Interactions of bile salts with a dietary fibre, methylcellulose, and impact on lipolysis. (1st March 2020) - Pabois, Olivia; Antoine-Michard, Amandine; Zhao, Xi; Omar, Jasmin; Ahmed, Faizah; Alexis, Florian; Harvey, Richard D.; Grillo, Isabelle; Gerelli, Yuri; Grundy, Myriam M.-L.; Bajka, Balazs; Wilde, Peter J.; et al.
Graphical abstract: Highlights: BS, NaTC and NaTDC, impact the rheological properties and gelation of MC. NaTDC has a greater impact on the viscoelasticity of MC, compared to NaTC. NaTDC desorbs from a MC-stabilised interface at lower concentrations than NaTC. Upon digestion, NaTDC destabilises more readily MC-stabilised emulsion droplets. During MC-stabilised emulsion digestion, NaTDC generates less FFA than NaTC. Abstract: Methylcellulose (MC) has a demonstrated capacity to reduce fat absorption, hypothetically through bile salt (BS) activity inhibition. We investigated MC cholesterol-lowering mechanism, and compared the influence of two BS, sodium taurocholate (NaTC) and sodium taurodeoxycholate (NaTDC), which differ slightly by their architecture and exhibit contrasting functions during lipolysis. BS/MC bulk interactions were investigated by rheology, and BS behaviour at the MC/water interface studied with surface pressure and ellipsometry measurements. In vitro lipolysis studies were performed to evaluate the effect of BS on MC-stabilised emulsion droplets microstructure, with confocal microscopy, and free fatty acids release, with the pH-stat method. Our results demonstrate that BS structure dictates their interactions with MC, which, in turn, impact lipolysis. Compared to NaTC, NaTDC alters MC viscoelasticity more significantly, which may correlate with its weaker ability to promote lipolysis, and desorbs from the interface at lower concentrations, which may explain its higher propensity to destabilise emulsions.